Level Up: A Study of Achievement Seekers in Battlefield 3 - Wiradinata, Irvan (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This research aimed to observe the effects of player’s achievement orientation on four features, namely player’s age, play hours, personality traits and nationality. Player’s achievement orientation is determined by the player’s in-game behavior in obtaining reward features in Battlefield 3.Design/methodology/approach: We used players’ in-game statistics and questionnaire data. The data were gathered using ‘PsyOps’ – a research-based website.Findings: With regards to the four features: 1) age - the results show that there is a difference in reward characteristics collected by young and adult players. Younger players tend to be more interested in rewards that require exceptional skills. Meanwhile, older players appeared to be more interested in rewards that are based on time employment; 2) play hours - the logarithmic regression showed that the reward feature could explain 64.4% of the variance in play hours feature. In addition to this, we also revealed the possibility to measure a player’s achievement orientation from their in-game behavior by developing the rating of a player’s achievement orientation; 3) personality traits - it was revealed that the Big Five personality traits do not appear to be a robust predictor of a player’s in-game behavior; and 4) nationality - we revealed that nationality did have a substantial impact on in-game achievement orientation, as shown by the Kruskal- Wallis H test.Research limitations/implications: The data collection process took place in summer of 2012, eight months after the game was releasedPractical implications: Moreover, a Mann-Whitney post-hoc test revealed that Finland has a significant difference of achievement orientation features compared to other countries tested. From tests performed, Finland is by far the most achievement-oriented country.Originality/value: This research could determine user’s achievement orientation, which can make them play the game better. This could be used in a daily life situation to make a student or worker to perform better at school and office respectively.